TRANSFORMASI KELEMBAGAAN DAN SIMPLIFIKASI REGULASI DI SEKTOR PERUMAHAN UPAYA PENCAPAIAN TARGET SWASEMBADA PAPAN - Khairul Umam; Muhammad Cahyadi (JOSH: Journal of Sharia, 2026)
The housing sector in Indonesia currently faces significant challenges due to the high housing backlog, which contrasts sharply with the government's ambitious targets for achieving housing self-sufficiency. This research aims to dissect the urgency of institutional transformation and regulatory simplification as fundamental strategies to overcome barriers in national housing provision. The primary issues identified include fragmented authority among government agencies, overlapping mandates between central and local governments, and licensing complexities that create legal uncertainty and high transaction costs for industry players. The research method employed is normative legal research with a statutory approach and a conceptual approach. Secondary data derived from legal literature and public policy are analyzed qualitatively to find solutions to bureaucratic deadlocks. The results indicate that institutional transformation through the establishment of an integrated housing authority can create more agile and focused policy orchestration. Furthermore, regulatory simplification through the harmonization of operational rules is proven to cut repetitive bureaucratic chains without compromising building quality standards. This study concludes that housing self-sufficiency can only be achieved if there is synergy between an organizational structure with strong authority and adaptive regulations. Strategic solutions offered include one-stop digital licensing and the establishment of a housing endowment fund managed by an independent body. The implementation of these policies is expected not only to accelerate the quantity of physical housing availability but also to ensure inclusivity for low-income communities. Thus, legal and institutional reforms are the primary keys to realizing a sustainable and independent national housing sector in the future.